Case report: MSI-H, EGFR mutation, and ground-glass nodules as diffuse pulmonary hematogenous metastases - He, Liuer; Li, Lin (Frontiers in Immunology, 2024)
Ground-glass nodules (GGNs) are generally considered an early stage of lung cancer. The imaging characteristics and curative efficacy of multiple GGNs as metastases remain unclear. Microsatellite instability-high (MSI-H) is a biomarker for immunotherapy. The therapeutic effect and prognosis for patients with MSI-H and Epidermal Growth Factor Receptor (EGFR)-sensitive mutation stays uncertain. Here, we report a case of a lung adenocarcinoma patient presenting with ground-glass metastases, MSI-H, and EGFR-sensitive mutation and provide clinical data on the efficacy and prognosis. We describe the predictive significance of carcinoembryonic antigen (CEA) for disease progression when there is inconsistency between treatment effectiveness and CEA changes.